The Competitive Advantages of Multi-Family Offices over Banks in Serving Wealthy Clients in Poland - Kozinska, Magdalena (European Journal of Family Business, 2021)
In Poland, the main players in serving wealthy clients are banks. Nevertheless, the number of multi-family offices (MFOs) has increased notably, raising questions whether they can become real competitors to the private banking divisions. Therefore, an analysis of the activity profile of multi-family offices and private banking in Poland was conducted. Additionally, a survey of multi-family offices enabled the evaluation of their perceived competitive positions. The level of development of MFOs in Poland is low and their market is in its infancy. MFOs operating in Poland are, however, considerably more flexible than banks operating in the field of private banking.